The Routledge history of food - Helstosky, Carol (London ; New York : Routlege, Taylor & Francis Group, 2015)
'Examines the history of economic, technological, and cultural interactions between cultures and the corresponding developments in food history, focusing on the period from 1500 to the present'--
Includes bibliographical references and index.
Keywords: Food -- History